Implementasi Pembelajaran Berdiferensiasi Pada Tingkat Anak Usia Dini di TK M Hilir Ismail Kota Bima - Mandasari, Dian; Salam, Agus; Ramadhan, Syahru; Dohny, Queencie (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2025)
The background of this research relates to the importance of implementing differentiated learning at the early childhood level in M Hilir Ismail Kindergarten, Bima City. Early childhood has a variety of characteristics, interests and different learning speeds, so it requires a learning approach that can meet their individual needs. Differentiated learning that accommodates these differences is believed to improve the quality of education and support holistic child development. The purpose of this research is to explore the application of differentiated learning in early childhood at M Hilir Ismail Kindergarten in Bima City and its impact on children's learning development. The type of research used is descriptive qualitative research, which aims to describe the phenomenon of differentiated learning in the classroom. Data collection techniques were conducted through observation, interviews with teachers and principals, and analysis of documentation of learning activities in the classroom. This research was conducted at M. Hilir Ismail Kindergarten located in Lelamase Village, East Rasana'e District, Bima City. The research was conducted for 2 months from February to March 2025. The data sources consist of teachers, students, and documentation of learning activities. The data analysis technique used is descriptive analysis, which identifies and interprets the patterns of the data obtained, to provide an in-depth picture of the implementation of differentiated learning. The results show that the implementation of differentiated learning at M Hilir Ismail Kindergarten is very effective in increasing children's involvement in learning. Through various activities such as theme-based educational games, ability-based learning groups, gross and fine motor activities, and children's stories and dramas, children get learning experiences that suit their abilities and interests. The contribution of this research provides insight into the effectiveness of differentiated learning in supporting early childhood development, as well as providing recommendations for the development of more inclusive and relevant learning methods.